1990
DOI: 10.1177/073428299000800308
|View full text |Cite
|
Sign up to set email alerts
|

Planning, Attention, Simultaneous, and Successive (PASS) Cognitive Processes as a Model for Intelligence

Abstract: This paper proposes an alternative theory of cognitive processing to serve as a model for reconceptualizing intelligence and facilitate evolution in this important area. The Planning, Attention, Simultaneous, and Successive (PASS) model, based on the work of A. R. Luria, is suggested as a broad conceptualization and framework for cognitive processing. Luria's view of these processes is presented in detail, as are experimental tasks developed by Das and Naglieri to measure these processes. An analysis of the WI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 71 publications
3
93
0
4
Order By: Relevance
“…The battery always included the spatial delayed response task and verbal and nonverbal intelligence measures (study 1: vocabulary and block design from the Wechsler Intelligence Scale for Children 3rd Edition [12], study 2: verbal-spatial relations and nonverbal matrices from the Das-Naglieri Cognitive Assessment Systems Battery [13], study 3: general information and spatial relations from the WoodcockJohnson III [14]). Results from measures unique to each study have been reported elsewhere (8,9).…”
Section: Testing Proceduresmentioning
confidence: 99%
“…The battery always included the spatial delayed response task and verbal and nonverbal intelligence measures (study 1: vocabulary and block design from the Wechsler Intelligence Scale for Children 3rd Edition [12], study 2: verbal-spatial relations and nonverbal matrices from the Das-Naglieri Cognitive Assessment Systems Battery [13], study 3: general information and spatial relations from the WoodcockJohnson III [14]). Results from measures unique to each study have been reported elsewhere (8,9).…”
Section: Testing Proceduresmentioning
confidence: 99%
“…This neuropsychological test for children was developed within the Planning, Attention and Simultaneous and Successive Processing (PASS) framework, which in turn is based on Luria's 'three principal functional units of the brain whose participation is necessary for any type of mental activity' [6, p. 36]. The PASS model has been described in detail by Cummins and Das [7], Das [8], and Naglieri and Das [6,9] and will not be elaborated on here. The previously mentioned research by Shaw-Ridley et al [4] has assessed over 70 monolingual children presenting with two broadly recognised types of language impairment: SLI and SPD.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of the study we adopted "PASS" neurocognitive theory (Planning, Attention, Simultaneous, Successive) [11][12][13] and the norm-referenced Cognitive Assessment System (CAS) [14]. Subtypes of children with DCD could be identified based on their performances on cognitive subscales of CAS, which was adopted to assess the children's cognitive abilities.…”
Section: Goals Of the Present Researchmentioning
confidence: 99%
“…Three major cognitive domains were used: a) Planning Scale, b) Attention Scale, and c) Simultaneous Coding Scale. The standard scores among the individual Scales have relevance to successes and failures in specific areas of academic performance [12,27]. Reliability and validity of the CAS are good and available in test's manual [27].…”
Section: Cognitive Assessmentmentioning
confidence: 99%